(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
An effect of lead acetate on growth and development of F. hygrometrica gametophyte and indexes of oxidative stress is studied. The toxic effect of lead ions is revealed on all stages of gametophyte development with most sensitivity during gametophore bud formation. Increasing of malonic dialdehyde and carbonylproteins content depending on the age of the moss gametophyte F. hygrometrica is established.